Evaluation in Vitro and in Vivo Toxicity of Synthesized Zinc Oxide Nanoparticles Against Streptococcus Oralis - Zahraa Jamal Saleem, Mais E. Ahmed, Mazin K. Hamid (Pakistan Journal of Medical & Health Sciences, 2022)
In the current study, an antibacterial activity of synthesized zinc oxide nanoparticle ( ZnO NPs) at different concentrations (16,32,64,256,512) µg/ml has been evaluated in vitro (well- diffusion method) against Streptococcus spp. that cause dental caries. The results demonstrated that ZnO had anti-Streptococcus activity especially at 64 µg/ml. Moreover, several methods have been performed such as EDS, atomic force microscope (AFM) to characterize ZnO NPs features such as EDS, atomic force microscope (AFM), X-ray diffraction (XRD), and TEM to ensure the features and size of ZnO nanoparticles. These techniques revealed that the average size of ZnO was about 30.52nm with hexagonal shape, and the UV-visible results demonstrated the big was determined at 340.8 mm, and the function of the ZnO NPs caused toxicity with inside the IC50 values of the HdFn cells. These data proved the biological activity of ZnO NPs against Gram-positive pathogens with less toxic effect on liver and spleen cells of rats.